Open-Wedge High Tibial Osteotomy: RCT 2 Years RSA Follow-Up - Lind-Hansen, Thomas Bruno; Lind, Martin Carøe; Nielsen, Poul Torben; Laursen, Mogens Berg (The Journal of Knee Surgery, 2016)
We investigated the influence of three different bone grafting materials on stability and clinical outcome of the healing open-wedge high tibial osteotomy (OW-HTO) with immediate partial weight bearing. A total of 45 (3 × 15) patients were randomized to injectable calcium phosphate cement (Calcibon; Biomet-Merck Biomaterials GmbH, Darmstadt, Germany), local bone autograft, or iliac crest autograft. Stability of the bony healing was evaluated with radiostereometric analysis (RSA) up to 24 months postoperatively. Clinical outcome was evaluated with the knee injury and osteoarthritis outcome score (KOOS). RSA revealed translations and rotations close to zero regardless of bone grafting material, with no statistically significant differences between the groups. Clinically, the Calcibon group had lower quality of life KOOS subscore at 2 years follow-up. We conclude that with a stable implant and 6 weeks of partial weight bearing, local autografting is sufficient to achieve solid bone consolidation following OW-HTO.
Keywords: HTO; bone graft materials; RSA; OA